KARAKTERISTIK PASIEN BATU SALURAN KEMIH DI RUMAH SAKIT MARTHA FRISKA PULO BRAYAN MEDAN TAHUN 2015 s/d 2017 - Poniyah Simanullang (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Darma Agung (LPPM_UDA), 2019)
Urinary tract stone is one of the three most common diseases in the field of urology after urinary tract infections and prostate benign enlargement. This disease usually occurs at the age of 60 – 69 years. Urinary tract stones in men 3 – 4 times more than women. The location of urinary tract stones in the kidneys is most often found. Actions that are often performed are non-invasive actions. The purpose of this study was to determine the characteristics of urinary tract stone patients at the Martha Friska Pulo Brayan Medan Hospital in 2015 until 2017. The type of research used is descriptive research. The population in this study is patients suffering from urinary tract stones in Martha Friska Hospital in 2015 to 2017 as many as 1579 people and the sample of this study is 316 people. The sampling technique is done by simple random sampling. The results show that the majority of urinary tract stones is happened at the age of 30 – 50 years, male gender, entrepreneurial work, location of stones in the ureter, medical management of URS (Ureteronoscopy). It is recommended for the Medan Martha Friska Hospital especially health workers to provide information or explanations for prevention of urinary tract stones and it is expected that completeness and uniformity in the status of patients is considered for the benefit of recording and reporting on the patient's condition.